Detection and homology analysis of carbapenem resistant Acinetobacter baumannii resistance gene - Huang, Hua-Liang; Li, Yue-Yu; Guo, Hong-Bo (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: To explore the carrying status and homology of carbapenem resistant Acinetobacter baumannii (CRAB) in our hospital. Methods: From January 2015 to December 2017, 52 strains of acinetobacter baumannii isolated from the bacteria room of the clinical laboratory of Baogang hospital in Inner Mongolia were selected as the research object. K-B disk diffusion method and Vitek-2 were used to determine the drug sensitivity of Acinetobacter baumannii. The drug resistance gene was detected by polymerase chain reaction (PCR) and its homology was analyzed by pulsed field gel electrophoresis (PFGE). Results: Except for Cefoperazone / sulbactam, other antibiotics were resistant to ab. The detection rate of drug resistance gene class C β-lactamases (ADC) was 100%, and the higher detection rates of other drug resistance genes were class D β-lactamases (OXA)-51 (36 strains, 90.0%),disinfectant gene qacE△1-sull (32 strains, 80.0%), and klebsiella pneumoniae carbapenemase (KPC) gene was not detected. 2-8 drug resistance genes were detected in each CRAB strain, and the strains with 6 drug resistance genes were the most (15 strains, 37.5%); Among the detected drug-resistant gene combinations, ADC+OXA-23 + OXA-51 gene was detected at the same time (29 strains, 72.5%), followed by ADC+ intl1 + qacE △ 1-sull gene (26 strains, 65.0%), ADC + qacE △ 1-sull + ant (3 '') -i gene (19 strains, 47.5%), and 11 strains (27.5%). There were 19 different types in PFGE homology test, each type was 1-9 strains, including 9 strains of A5 type and 8 strains of A18 type, mainly from intensive care unit. Conclusion: CRAB in the hospital is highly resistant to common clinical antibiotics. OXA-23 and OXA-51 genes are most likely to be the main factors causing drug resistance of Acinetobacter baumannii in the hospital. Homology analysis showed that there was CRAB nosocomial infection transmission in different wards of the hospital.